Influence of Pre and In-Service Training Programs of the Kindergarten Teachers in the Implementation of the Kindergarten Curriculum - Resa Dee Santos (Philippine Association of Institutions for Research, Inc., 2023)
This study investigated the significant relationship between the extent of pre-and in-service training of kindergarten teachers and their performance ratings in 2020-2022. The profile of teachers was identified, which focuses on educational attainment, number of years in teaching and in-service and pre-service seminars attended by teachers, the extent of the pre and in-service trainings, and their performance ratings in two consecutive years. This study employed a non-experimental correlational research design, and the respondents were the 385 kindergarten teachers in the Division of Sarangani. The results showed that 70.87% are non-Early Childhood Education graduates and 17.47% of the kindergarten teachers are pursuing master's degrees, not specializing in Early Childhood Education, and 7.77% are pursuing master's degrees specializing in Early Childhood Education. Findings revealed that the pre-service trainings of kindergarten teachers are less extensive. However, the in-service trainings for kindergarten teachers are highly extensive. The performance rating of the kindergarten teachers in the two school years is Very Satisfactory. There was a strong significant relationship between the extent of pre and in-service teachers' training and their performance rating in the two school years. With the results of the study, it is recommended that teachers teaching kindergarten should pursue a master's degree specializing in Early Childhood Education. Also series of trainings and seminars should also be conducted to help kindergarten teachers improve their performances.